2019
DOI: 10.1136/bcr-2018-225803
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic granuloma gravidarum: a case in the nasal cavity and the use of MRI as a preoperative surgical aide

Abstract: Pyogenic granuloma gravidarum is a benign fibrovascular proliferative lesion usually involving the oral gingivae in pregnant patients. While it also occurs, although less frequently, on other oral sites such as lips, tongue and palate, it is relatively unusual to find it in the nasal cavity. Furthermore, lesions normally involute spontaneously after childbirth. For persistent lesions requiring surgical management, imaging has historically been limited to CT. This case is notable not only for its uncommon locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Usually, pyogenic granuloma gravidarum affects the oral mucosa, especially the gingiva, while the nasal cavity is an unusual site of location with a reported incidence of 7%-10% (1). Most cases of nasal pyogenic granuloma occur on the nasal septum (76%) and the inferior turbinate (12%-20%) (9,16). In our case, the lesion was located on the anterior part of the nasal septum.…”
Section: Case Reportmentioning
confidence: 46%
See 3 more Smart Citations
“…Usually, pyogenic granuloma gravidarum affects the oral mucosa, especially the gingiva, while the nasal cavity is an unusual site of location with a reported incidence of 7%-10% (1). Most cases of nasal pyogenic granuloma occur on the nasal septum (76%) and the inferior turbinate (12%-20%) (9,16). In our case, the lesion was located on the anterior part of the nasal septum.…”
Section: Case Reportmentioning
confidence: 46%
“…When it occurs in pregnant women, it is usually referred as pyogenic granuloma gravidarum or "pregnancy tumor". Although the exact etiology remains unclear, nasal cavity trauma and increased levels of estrogen and progesterone have been usually implicated in the development of pyogenic granuloma (16). Other risk factors that have been described in the literature include preexisting skin conditions, viral oncogenes, underlying microscopic arteriovenous malformations and angiogenic growth factor production (4,9).…”
Section: Case Reportmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Hence, it has been suggested that excision is indicated only in cases that fail to involute. 8 Surgical excision is the preferred treatment for lobular capillary haemangioma of the nasal cavity. Other methods include electrocautery, laser therapy, and embolization.…”
Section: Discussionmentioning
confidence: 99%